1993
DOI: 10.1037/0022-006x.61.3.455
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing motivation for change in problem drinking: A controlled comparison of two therapist styles.

Abstract: To investigate the impact of counselor style, a 2-session motivational checkup was offered to 42 problem drinkers (18 women and 24 men) who were randomly assigned to 3 groups: (a) immediate checkup with directive-confrontational counseling, (b) immediate checkup with client-centered counseling, or (c) delayed checkup (waiting-list control). Overall, the intervention resulted in a 57% reduction in drinking within 6 weeks, which was maintained at 1 year. Clients receiving immediate checkup showed significant red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
467
3
21

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 641 publications
(511 citation statements)
references
References 29 publications
20
467
3
21
Order By: Relevance
“…Whereas earlier MI coding manuals could only predict the lack of behaviour change based on resistance language (i.e. sustain talk ;Miller, Benefield, & Tonigan, 1993), the adapted language categorization by Amrhein et al (2003) allows predictions of behaviour change in substance abuse. In summary, the coding of language in dyadic interactions into change and sustain talks has only been applied in therapeutic settings.…”
Section: Recipient Behaviours In Change Conversationsmentioning
confidence: 99%
“…Whereas earlier MI coding manuals could only predict the lack of behaviour change based on resistance language (i.e. sustain talk ;Miller, Benefield, & Tonigan, 1993), the adapted language categorization by Amrhein et al (2003) allows predictions of behaviour change in substance abuse. In summary, the coding of language in dyadic interactions into change and sustain talks has only been applied in therapeutic settings.…”
Section: Recipient Behaviours In Change Conversationsmentioning
confidence: 99%
“…Valle (1981) reported similar findings from a study of client-centred counselling for alcohol problems. A further remarkable finding was reported by Miller, Benefield & Tonigan (1993) who showed that half the variance in treatment outcome could be predicted by the degree to which the therapist had confronted the client, in many ways the opposite of empathy, during treatment sessions.…”
Section: Therapist Factorsmentioning
confidence: 76%
“…En el caso concreto del tabaquismo la mayoría de los fumadores no quieren dejar de fumar. La entrevista motivacional (EM) se ha propuesto como un procedimiento útil para incrementar la motivación intrínseca del individuo para el cambio (Bien, Miller y Boroughs, 1993;Bien, Miller y Tonigan, 1993;Miller, 1983;Miller y Rollnick, 1991.…”
Section: Introductionunclassified
“…En el caso concreto del tabaquismo la mayoría de los fumadores no quieren dejar de fumar. La entrevista motivacional (EM) se ha propuesto como un procedimiento útil para incrementar la motivación intrínseca del individuo para el cambio (Bien, Miller y Boroughs, 1993;Bien, Miller y Tonigan, 1993;Miller, 1983;Miller y Rollnick, 1991.La EM se define como un estilo de comunicación, centrado en el cliente, dirigido a un objetivo, que pretende provocar un cambio en el comportamiento, ayudando a resolver las propias motivaciones para cambiar de los clientes (Miller y Rollnick, 2002 La mayoría de los fumadores que acuden a tratamiento se encuentran en el estadio de precontemplación y contemplación (Prochaska, Velicer, Prochaska y Johnson, 2004), es decir, todavía no han considerado la posibilidad de abandonar el consumo de tabaco a corto plazo. En este sentido, la literatura señala que la EM está particularmente indicada para trabajar con aquellos clientes que se muestran ambivalentes y que están menos motivados para cambiar (Heather, Rollnick, Bell y Richmond, 1996;Hettema, Steele y Miller, 2005).…”
unclassified